2013
DOI: 10.1371/journal.pone.0057190
|View full text |Cite
|
Sign up to set email alerts
|

The Poultry-Associated Microbiome: Network Analysis and Farm-to-Fork Characterizations

Abstract: Microbial communities associated with agricultural animals are important for animal health, food safety, and public health. Here we combine high-throughput sequencing (HTS), quantitative-PCR assays, and network analysis to profile the poultry-associated microbiome and important pathogens at various stages of commercial poultry production from the farm to the consumer. Analysis of longitudinal data following two flocks from the farm through processing showed a core microbiome containing multiple sequence types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 80 publications
10
87
3
Order By: Relevance
“…This notion is supported by the observation that phylogenetically related microbes have a tendency to positively co-occur (Lozupone et al, 2012). Recent studies suggest that the microbial relationships shown in correlation interaction networks can be used to determine drivers in environmental ecology (Ruan et al, 2006;Steele et al, 2011;Zhou et al, 2011;Lima-Mendez et al, 2015) or contribution to habitat niches or disease (Chaffron et al, 2010;Arumugam et al, 2011;Greenblum et al, 2012;Oakley et al, 2013;Goodrich et al, 2014;Buffie et al, 2015). Correlation is also a powerful tool to help researchers with hypothesis generation, such as determining which interactions might be biologically relevant in their system, and should be given further study (for example, through co-culturing or whole-genome sequencing).…”
Section: Introductionmentioning
confidence: 93%
“…This notion is supported by the observation that phylogenetically related microbes have a tendency to positively co-occur (Lozupone et al, 2012). Recent studies suggest that the microbial relationships shown in correlation interaction networks can be used to determine drivers in environmental ecology (Ruan et al, 2006;Steele et al, 2011;Zhou et al, 2011;Lima-Mendez et al, 2015) or contribution to habitat niches or disease (Chaffron et al, 2010;Arumugam et al, 2011;Greenblum et al, 2012;Oakley et al, 2013;Goodrich et al, 2014;Buffie et al, 2015). Correlation is also a powerful tool to help researchers with hypothesis generation, such as determining which interactions might be biologically relevant in their system, and should be given further study (for example, through co-culturing or whole-genome sequencing).…”
Section: Introductionmentioning
confidence: 93%
“…Data from Tillman et al . () and Wise & Siragusa () are re‐analyzed from data included in (Oakley et al ., ) representing 8 and 10 birds, respectively. Kogut et al .…”
Section: Spatial Variabilitymentioning
confidence: 99%
“…In terms of commercial poultry production and processing, microbial community studies have focused on gastrointestinal tract (Sekelja et al, 2012;Yeoman et al, 2012;Stanley et al, 2013;Sergeant et al, 2014), fecal (Sekelja et al, 2012;Singh et al, 2012;Stanley et al, 2015), litter (Dumas et al, 2011;Smith et al, 2014), carcass (Oakley et al, 2013), and raw retail poultry meat (Nieminen et al, 2012) samples; however, no study has specifically characterized commercial scalder and chiller water tank microbiomes. Therefore, in this study, Illumina MiSeq-based 16S rRNA-based pyrosequencing was used to characterize final scalder and chiller water tank microbiomes and investigate their dynamics during a typical commercial processing d, not only in terms of general microbial populations, but also to specifically target poultryassociated bacterial pathogens and spoilage organisms.…”
Section: Introductionmentioning
confidence: 99%